Acute Onset Symptomatic Polycythaemia Vera - DP., Busuttil (Journal of Hematology and Oncology Research, 2016)
A case of acute symptomatic polycythaemia vera is presented with diagnostic work‑up, risk stratification, and acute management considerations. The discussion highlights thrombotic risk and cytoreductive strategies.
Keywords: polycythaemia vera; myeloproliferative neoplasms; marginal zone lymphoma; thromboembolism